Difusão da pílula anticoncepcional no Brasil, 1962-1972: a mídia e os livros didáticos - Santana, Joelma Ramos (2016)
The present study sought to analyze contextual and historiographical aspects related with the diffusion of oral contraception, particularly among women, along the period of its introduction and initial commercialization in Brazil (1962-1972). Therefore we analyzed how the information on the mode of action of the pill on the female body, related implications and alleged risks and benefits was divulgated. For that purpose the sources used were magazines and journals commonly read at that time and the biology textbooks used in secondary schools. The result was a mapping of the contemporary scientific ideas on oral contraception and the socio-historical framework that circumscribed its divulgation. Our study shows that while the arrival of the pill in Brazil was a cause of heated debate, it dealt less with scientific than with moral, political and religious issues. The school textbooks, in turn, continued to convey information on reproductive anatomy and physiology outdated in more than 50 years. If mentioned at all, the possibility to control fertility was discussed within the context of eugenic, hygienist or religious ideas